PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PENGADILAN TINGGI PALEMBANG DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Yuniasthy, Evi; Manisah, Manisah; Nasir, Nasir (Postgraduate Management Journal, 2025)
This study aims to analyze the influence of competence and work discipline on employee performance, both directly and indirectly, with motivation as an intervening variable, among employees of the Palembang High Court. The research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 82 permanent employees and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of the SmartPLS application. The results show that competence and work discipline have a significant effect on employee performance, both directly and indirectly, through work motivation as an intervening variable. Work motivation is also proven to have a positive and significant impact on improving employee performance. The implications of these findings highlight the importance of regularly evaluating the effectiveness of policies related to competence, work discipline, and motivation, and using the evaluation results as a basis for revising managerial policies to remain adaptive to changes in the work environment and employee needs.